Intimate Partner Violence and Same-Sex Couples: Examining the Antecedents of the Helping Intentions of Bystanders. Issue 21 (November 2021) - Pagliaro, Stefano; Paolini, Daniele; Pacilli, Maria Giuseppina
Researchers interested in intimate partner violence (IPV) have focused primarily on male-against-female cases. We conducted two experimental investigations to examine the influence of moral evaluation, attribution of responsibility, and right-wing authoritarianism (RWA) on the willingness of bystanders to provide help to the victim in an IPV case involving a same-sex couple. Study 1 ( N = 195) surveyed a heterosexual participant sample, and Study 2 ( N = 120) surveyed a sample of gay and lesbian participants. In both studies, participants read a fictitious article describing an alleged IPV episode that occurred either in a male–male or a female–female couple. Each participant read an article describing one of two versions of a case of IPV: In one account, the victim admitted to infidelity and in the other, the victim did not confess to infidelity. The participants subsequently evaluated the victim and expressed their willingness (or lack thereof) to support and provide help to the injured party. In both studies, participants in the condition that included the admission of infidelity assessed the victim to be less moral and more responsible for the violent episode. Consequently, participants of both studies expressed lesser willingness to provide help to the victim. Moreover, in Study 1, the relationship between the admission of infidelity and the respondents' willingness to support the victim was moderated by RWA. Particularly, the admission of infidelity by the victim reduced the respondents' willingness to extend support only when they reported a medium to a high level of RWA ideology. By focusing specifically on same-sex IPV cases, this study contributes to a more comprehensive understanding of the reactions of witnesses with regard to IPV. Furthermore, it provides evidence about the underlying mechanisms mitigating the intervention of bystanders in such cases and identifies boundary conditions that exacerbate their (un)willingness to intervene.